2013
DOI: 10.12669/pjms.292.3283
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology, treatment patterns and long-term outcomes of tooth avulsion in children and adolescents

Abstract: Objective: Tooth avulsion constituting an emergency for children and adolescents necessitates management approaches ensuring the survival of avulsed teeth. The aim of this study was to determine the causes of tooth avulsion and to examine some factors affecting the clinical & radiographic assessment of their prognosis after replantation. Methodology: The study sample was created by using archival records of patients who were referred to the Suleyman Demirel University, Faculty of Dentistry, Department of Pedod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 17 publications
1
26
0
11
Order By: Relevance
“…Falls are considered the most important aetiological factor for dental trauma during the primary and permanent dentition periods . The other factors resulting in dental injuries are collisions, sport, traffic accidents and violence . The majority of the dental trauma incidents in young children occur at home, in parks and at kindergarten, whereas adolescents are more commonly subject to dental trauma during sports activities, traffic accidents and violent incidents outside the home …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Falls are considered the most important aetiological factor for dental trauma during the primary and permanent dentition periods . The other factors resulting in dental injuries are collisions, sport, traffic accidents and violence . The majority of the dental trauma incidents in young children occur at home, in parks and at kindergarten, whereas adolescents are more commonly subject to dental trauma during sports activities, traffic accidents and violent incidents outside the home …”
Section: Introductionmentioning
confidence: 99%
“…5,[8][9][10][11] The other factors resulting in dental injuries are collisions, sport, traffic accidents and violence. [12][13][14][15] The majority of the dental trauma incidents in young children occur at home, in parks and at kindergarten, whereas adolescents are more commonly subject to dental trauma during sports activities, traffic accidents and violent incidents outside the home. 12,16,17 The time elapsed from when the dental trauma occurs to when the patient arrives at the dental clinic and receives emergency intervention is one of the most important factors in the prognosis of the affected tooth/teeth.…”
mentioning
confidence: 99%
“…Histologically, replanted teeth exhibit four main patterns of periodontal healing: normal periodontal ligament healing, healing with surface resorption, healing with ankylosis, and healing with inflammatory resorption . In cases of delayed replantation, ankylosis, that characterized by fusion of the alveolar bone and cementum, is generally inevitable because of the absence of viable PDL cells and also there is an underestimated risk of inflammatory . It seems that the prevention or delaying of ankylosis relies procedures such as treatment of root surface, root‐canal therapy, and systemic antibiotic regimen .…”
Section: Discussionmentioning
confidence: 79%
“…2 In cases of delayed replantation, ankylosis, that characterized by fusion of the alveolar bone and cementum, is generally inevitable because of the absence of viable PDL cells and also there is an underestimated risk of inflammatory. 2,20,37,38 It seems that the prevention or delaying of ankylosis relies procedures such as treatment of root surface, root-canal therapy, and systemic antibiotic regimen. 23 In this case, there was no ankylosis sign in radiograph or clinic 16 years after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The International Association of Dental Traumatology (IADT) identifies avulsion as one of the most serious dental injuries due to its implications for tooth loss and sequelae following treatment . Despite only accounting for 0.5–16% of all traumatic dental injuries (TDIs), avulsed teeth are considered the TDI with the poorest long‐term survival rates – with up to 64.5% of teeth lost at the point of injury . A meta‐analysis found that the median age at which a permanent tooth experienced a TDI was 13.8 years, implicating school‐aged children as a high‐risk group for TDIs and avulsion.…”
Section: Introductionmentioning
confidence: 99%